Experimental Study on the Calibration of Microparameters of Dolomite in the Barun Open-Pit Mine on the Basis of the Parallel Bond Model - Zhiheng Dang; Zuoming Yin; Desheng Wang; Mingyu Fu; Qi Yin (Advances in Civil Engineering)
The microparameter calibration of the particle flow parallel bond model (PBM) is mostly based on a uniaxial compression test. The microparameters calibrated only by uniaxial compression tests cannot be directly used to study the mechanical properties of rocks with surrounding pressure conditions. To analyze the relationship between the macroparameters and microparameters in the model and select appropriate particle flow model parameters, this study conducted a particle flow numerical simulation experiment based on the basic test principles of the uniaxial compression, Brazilian splitting, and triaxial compression tests. An orthogonal experimental design was performed for the calibration of the microparameters of the particle flow PBM, and multifactor analysis of variance was used to screen out the factors that have a considerable influence on the experimental indicators. Regression analysis was performed on the significant influencing factors and test indicators, and the corresponding linear and nonlinear relationships between the macroparameters and microparameters were obtained. Lastly, the microparameters of the model were determined in accordance with the macroparameters of the mechanical test of the Barun open-pit mine dolomite, and a numerical simulation test was conducted. Simulation test results were consistent with the actual test results, thus providing a basis for a subsequent numerical simulation study on the mechanical properties of dolomite.